Investigations of Oil-Free Support Systems to Improve the Reliability of ORC Hermetic High-Speed Turbomachinery - Tkacz, Eliza; Kozanecka, Dorota; Kozanecki, Zbigniew; Miazga, Kacper (Wydawnictwo Politechniki Łódzkiej ; Katedra Dynamiki Maszyn - Wydział Mechaniczny Politechniki Łódzkiej, 2011)
The design of a small turbo-generator to produce electricity in the range from a few kWs requires the use of an aerostatic or aerodynamic gas bearing system. The theoretical analysis and the experimental test at the present stage of the study show that such highly rotating constructions are feasible. The problem consists in the optimal design selection from the viewpoint of the machine reliability and the adjustments are connected to the diminution in static thrust and lateral loads of the bearings by a correct design of the turbine flow structure and a correct selection of the gas bearing type.
Keywords: oil-free support systems; hermetic high-speed turbomachinery; ORC; bezolejowe systemy wsparcia; hermetyczna szybkobieżna maszyna wirnikowa